2003
DOI: 10.1017/s1446788700003153
|View full text |Cite
|
Sign up to set email alerts
|

Biseparating linear maps between continuous vector-valued function spaces

Abstract: LetA\ y be compact Hausdorff spaces and £, F be Banach spaces. Alinearmap T :is separating if Tf, Tg have disjoint cozeroes whenever / , g have disjoint cozeroes. We prove that a biseparating linear bijection T (that is, T and T~l are separating) is a weighted composition operator Tf = hf o Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 16 publications
1
26
0
Order By: Relevance
“…The following example, adapted from [10], shows that, in the vector-valued setting, unlike in the complex-valued case ( [9]), the automatic continuity of T cannot be obtained from its disjointness preserving property, even if T is a biseparating bijection.…”
Section: Disjointness Preserving Maps On Vector-valued Group Algebrasmentioning
confidence: 99%
See 1 more Smart Citation
“…The following example, adapted from [10], shows that, in the vector-valued setting, unlike in the complex-valued case ( [9]), the automatic continuity of T cannot be obtained from its disjointness preserving property, even if T is a biseparating bijection.…”
Section: Disjointness Preserving Maps On Vector-valued Group Algebrasmentioning
confidence: 99%
“…(see, for example, [1,2,3,4,5,7,8,13,16]). In recent years, certain attention has been given to such maps when defined on spaces of vector-valued continuous functions (see, e.g., [10,14]). However, we do not know much about disjointness preserving maps on vectorvalued settings in comparison with scalar-valued contexts and something similar can be said with regard to (algebra) homomorphisms between vector-valued group algebras.…”
Section: Introductionmentioning
confidence: 99%
“…(ii) The following example borrowed from [11,Example 2.4] shows that in the above results when E (and so F ) is not a finite dimensional space, common zeros preserving maps need not be continuous (see also [1,Remarks(2)…”
Section: Case 2 T Smentioning
confidence: 99%
“…In the case where X, Y are metric spaces and E, F are normed spaces, a complete description of linear bijections T : A(X, E) → A(Y, F ) between certain subspaces of C(X, E) and C(Y, F ), satisfying the weaker condition Z(f ) ∩ Z(g) = ∅ ⇐⇒ Z(T f ) ∩ Z(T g) = ∅, for all f, g ∈ A(X, E), is given in [7] and then some extensions of the previous results are obtained. In [18], among other things, the authors considered maps preserving zero set containments, which dates back to [11]. Indeed, they characterized linear bijections T : C(X, E) → C(Y, F ) such that…”
Section: Introductionmentioning
confidence: 99%
“…Later advances saw versions of the theorem of Gelfand and Kolmogorov on other function algebras as well as generalizations to biseparating maps, i.e., bijective maps that preserve disjointness of functions in both directions. For instance, see [3,4,5,15,18,20,22]. As a vector lattice, Kaplansky [21] showed that C(X) determines a compact Hausdorff space X up to homeomorphism.…”
mentioning
confidence: 99%